Instagram as Public Relations Media Relations N3 Unique Creativity Event Organizer In Improving Brand Image - Hariyadi, Nanda Widyanita; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
This research uses descriptive qualitative methods to find data on the role of N3 Unique Creativity Event Organizer's public relations in improving brand image through Instagram. It emphasizes the theory used to reach the conclusion stage more. N3 Unique Creativity Event Organizer is a professional service company responsible for designing, holding, and managing every aspect of an event. Data collection was carried out through observation and interviews, and data analysis was performed using data reduction, data presentation, and conclusion drawing. This research aims to discover Instagram as a public relations media for N3 Unique Creativity Event Organizer to improve brand image. The results of this study are successful in building a brand image as evidenced by having become a reference place when someone realizes an event, increasing the number of Instagram viewers and followers each month, increasing the number of clients, and more and more cooperation offers.